Structural Integrity and Failure - Oyguc, Resat; Tahmasebinia, Faham (IntechOpen, 2021)
Structural integrity and failure assessment have been considered by many fields of engineers as it is a multi-disciplinary concept. The assessment procedure vitally ensures that structural elements will remain functional throughout their service lives. Structural failure refers to the loss of structural integrity by means of loss at the component- or system-level elements. The main concern of integrity assessment is that a structural failure may be avoided at the service level by designing the structure to withstand its designated loads. Hence, for satisfactory structural performance, structural safety, failure, and interaction between them should be considered throughout the design and analysis stages. This book is a collection of chapters that provide the researcher with a comprehensive perspective on structural integrity and its sub-disciplines.